An investigation on the measurement of instantaneous temperatures in laser assisted additive manufacturing by thermal imagers. (August 2020) - Kayacan, Mevlüt Yunus; Yılmaz, Nihat
Highlights: In-situ temperature measurement was performed during powder bed fusion AM. An equation was generated for the accurate temperature measurement of PBF-AM. The predictive mathematical model and finite element analysis were compared. Abstract: Powder bed fusion additive manufacturing processes has started to be investigated by means of temperature distribution and change on parts, since problems such as residual stresses, deformations, microstructural differences and lack of mechanical properties were observed due to temperatures of parts during manufacturing. In the current studies, thermal cameras were used to analyze thermal history of parts. Depending on the accuracy of thermal cameras, temperature values were varied. In this study, a mathematical model which was supported by the data of experimental tests was developed to obtain increased accuracy. Melt pool temperatures were predicted by using the model which consisted of average temperature and extrapolated measurement area approaches. Melt pool temperatures were calculated ranging between 1700 and 2800 °C. Besides, temperature-dependent cooling rate was considered in the model to improve accuracy of temperature measurement. In addition, finite element analysis of manufacturing process was performed to verify results. Comparison between results of the mathematical equations and finite element analysis showed the accuracy as minimum 85% and maximum 98%. A trusted equation was generated to calculate melt pool temperatures by using an ordinary thermal imager.